Light-Responsive Enzyme-Loaded Nanoparticles for Tunable Adhesion and Mechanical Wound Contraction - Ko, Junghyeon; Kim, Hyeon-Jin; Kim, Jeong-Uk; Oh, Seh Ri; Kang, Tae Hoon; Byun, Junghwan; Lee, Uk-Jae; Ma, Minglin; Kim, Su-Hwan; Kim, Byung-Gee; Hwang, Nathaniel S. (John Wiley & Sons Ltd., 2026)
Tissue adhesives have emerged as minimally invasive tools for wound closure and the secure attachment of biomaterials to tissue surfaces. However, the development of on-demand, tunable adhesives remains limited, restricting their adaptability to dynamic and complex tissue interfaces. In this study, a spatiotemporally light-responsive and synergistic system: photoactivatable tyrosinase-loaded mesoporous polydopamine nanoparticles (MPDA_PaTy) is presented. Upon ultraviolet (UV) irradiation, MPDA_PaTy enables precise modulation of adhesive strength, achieving up to 3.7-fold enhancement with increasing irradiation time. This tunability facilitates effective tissue adhesion for in vivo wound closure in mouse incision models and enhances the mechanical contraction of circular wounds by anchoring pre-stretched hydrogels, as demonstrated in both ex vivo and in vivo models. Finite-element modeling further confirms the hydrogel's wound-contraction capability. These results demonstrate that MPDA_PaTy is a versatile, tunable bioadhesive with significant potential for advanced tissue engineering applications.